Effects of nesting and swaddling on the sleep duration of premature infants hospitalized in neonatal intensive care units - Zahra Abdeyazdan; Maryam Mohammadian-Ghahfarokhi; Zohreh Ghazavi; Majid Mohammadizadeh (Wolters Kluwer Medknow Publications, 2016)
Background: In neonatal intensive care unit (NICU), neonatal sleep is disrupted due to different factors. Due to the critical role of sleep in premature infants' brain development, this study aimed to investigate the effect of nesting and swaddling on the sleep duration of premature infants hospitalized in NICUs. Materials and Methods: In a crossover clinical trial, 42 preterm infants who met the inclusion criteria were enrolled. They were randomly assigned to two groups of nest-swaddle and swaddle-nest. Sleep status was evaluated by observation and use of Prechtl's criteria. Then, durations of total sleep time (TST) and quiet sleep time (QST) were recorded. Data were analyzed using repeated measure analysis of variance (ANOVA). Results: Mean values of TST and QST during nesting and also swaddling periods were significantly higher than in the control period in both groups (P < 0.001). Mean values of TST and QST in the swaddling period were higher than in the nesting period in both groups, However, these differences were not significant (P = 0.245). Conclusions: Both swaddling and nesting could significantly increase the duration of TST and QST, compared to the control. There were no significant differences between the effects of these interventions on TST and QST. Therefore, using any of these methods is suggested to improve infants' quality of sleep in NICU, with respect to the ward policies.